2013
DOI: 10.1111/zsc.12042
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic species in the cosmopolitan Bugula neritina complex (Bryozoa, Cheilostomata)

Abstract: Previous analyses of the mitochondrial gene cytochrome c oxidase subunit 1 (COI) and γ‐proteobacterial endosymbiont diversity have suggested that the marine bryozoan Bugula neritina is a complex of three cryptic species, namely Types S, D and N. Types D and N were previously reported to have restricted distributions along California (western USA) and Delaware and Connecticut (eastern USA), respectively, whereas Type S is considered widespread in tropical, subtropical and temperate regions due to anthropogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 62 publications
(122 reference statements)
2
45
1
3
Order By: Relevance
“…This species is able to attach to ship hulls [41] showing tolerance to heavy metals, such as copper and zinc present in several antifouling paints [55,72]. Bugula neritina is currently considered a species complex forming at least three different lineages (Type S, D and N) that also differ in their distributional patterns [49,71,73,74]. Type S is the most widely distributed, appearing in tropical, subtropical and temperate waters around the world, including the North-eastern Atlantic [49,50,71].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This species is able to attach to ship hulls [41] showing tolerance to heavy metals, such as copper and zinc present in several antifouling paints [55,72]. Bugula neritina is currently considered a species complex forming at least three different lineages (Type S, D and N) that also differ in their distributional patterns [49,71,73,74]. Type S is the most widely distributed, appearing in tropical, subtropical and temperate waters around the world, including the North-eastern Atlantic [49,50,71].…”
Section: Discussionmentioning
confidence: 99%
“…Bugula neritina is a widely known cosmopolitan bryozoan species since the eighteenth century [71], distributed in warm-temperature and subtropical coastal waters, known as an important component of the fouling communities colonizing artificial substrates (see historical review in Ryland, Bishop [50]). This species is able to attach to ship hulls [41] showing tolerance to heavy metals, such as copper and zinc present in several antifouling paints [55,72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular studies have recently shown that morphologically defined, B. neritina is a complex comprising at least three separate species (Fehlauer-Ale et al 2014). The complex is very widely distributed in tropical, subtropical and even temperate waters, and is an important fouling taxon dispersed anthropogenically (e.g., Ryland et al 2011).…”
Section: Remarksmentioning
confidence: 99%
“…B. neritina larvae frequently attach to boat hulls, and the species is regarded as one of the most widespread fouling bryozoans (Winston and Woollacott 2008). DNA sequencing of the mitochondrial gene cytochrome c oxidase I (COI) suggests that B. neritina is actually a complex of three cryptic species (Mackie et al 2006, Davidson & Haygood 1999, which may have distinct native ranges (Fehlauer-Ale et al 2014). Native and non-native boundaries for B. neritina therefore remain unclear, but a cosmopolitan distribution was reported for B. neritina as early as the 18 th century (Winston and Woollacott 2008), and its range is expanding (Winston and Woollacott 2008).…”
Section: Chapter I Introductionmentioning
confidence: 99%